Program Parenting di PAUD Avicena dan RA Nurul Iman Negeri Katon - Dea, Leli Fertiliana; Yusuf, Muhammad; Choirudin, Choirudin (CV. BImbingan Belajar Assyfa, 2025)
This community service program aimed to enhance parental involvement in early childhood education through a Participatory Parenting approach implemented at PAUD Avicena and RA Nurul Iman Negeri Katon. The study employed the Participatory Action Research (PAR) method, which involved teachers, parents, and lecturers in all stages of planning, implementation, observation, and reflection. The activities included training on effective communication, Islamic-based parenting, and parent–child play sessions. The results showed an increase in parental awareness and competence in applying positive parenting at home, as well as improved communication and collaboration between teachers and families. Children demonstrated more independent, cheerful, and cooperative behavior, while teachers gained valuable experience in supporting families and strengthening their roles as facilitators of family-based learning. The program proved that a participatory approach effectively strengthened the synergy between educational institutions and parents, contributing to the moral and character development of young children. The outcomes were expected to serve as a model for sustainable parenting programs that were contextual, collaborative, and grounded in Islamic educational values.